2011
DOI: 10.1542/peds.2011-0453
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Interventions to Enhance Influenza Vaccine Delivery to Adolescents

Abstract: Special efforts to promote influenza vaccination among rural, predominantly black students were associated with increased vaccination coverage. The school-based influenza vaccination intervention was associated with the highest levels of vaccination coverage. This study revealed the efficacy of school-based influenza education to improve vaccination rates among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…[37] Barriers to increased vaccination of school age children include, but are not limited to, vaccine supply limitations, need for extra office visits to get the yearly vaccine each season, and challenges of communication between primary care providers, subspecialists, schools, health departments, pharmacists and other influenza vaccine providers. [35;37;48]…”
Section: Discussionmentioning
confidence: 99%
“…[37] Barriers to increased vaccination of school age children include, but are not limited to, vaccine supply limitations, need for extra office visits to get the yearly vaccine each season, and challenges of communication between primary care providers, subspecialists, schools, health departments, pharmacists and other influenza vaccine providers. [35;37;48]…”
Section: Discussionmentioning
confidence: 99%
“…56,57,62,[64][65][66]84 Of these studies, five specifically targeted only children and adolescents 56,57,[64][65][66] as this age group is considered not only vulnerable in contracting certain infections, but can also be important vectors of spreading infectious diseases, amongst their peers, families and communities. This is particularly relevant in densely populated urban areas of LMICs.…”
Section: Reaching Vulnerable Populations and Health Equityrelated Issuesmentioning
confidence: 99%
“…Differences in the cost-effectiveness of specific venues were also noted by a few eligible studies. For example, Gargano et al 57 highlights that schoolbased vaccination clinics are potentially more costeffective than similar interventions within primary care physicians' offices or public clinics because of the ability to efficiently vaccinate large numbers of children. This study found that the efficacy of a multi-component school-based vaccination program on improving vaccination rates was greater than in the case of a similar program administered via local healthcare providers in clinical settings.…”
mentioning
confidence: 99%
“…In some areas, school located influenza vaccination (SLIV) programs have demonstrated that seasonal influenza vaccination rates were higher (more than 4.4 times in elementary, 2 times -in middle, and 1.7 times -in high school students) than in non-SLIV locations [22]. Multiple SLIV programs have been very effective .at achieving high vaccination rates [22][23][24][25][26][27]. Also, SLIV programs demonstrated protection not only to the vaccinated children, but also to their parents [22] and other members in the community [28].…”
Section: -2008mentioning
confidence: 99%